The 10 best-ever depression management techniques : understanding how your brain makes you depressed & what you can do to change it - Wehrenberg, Margaret (New York : W.W. Norton, 2010)
Drawing on cutting-edge neuroscience research presented in a reader-friendly way, Wehrenberg skillfully describes what happens in the brain of a depression sufferer and what specific techniques can be used to alter brain activity and control its range of disabling symptoms. Containing practical, take-charge tips from a seasoned clinician, this book presents the ten most effective strategies for moving from lethargy into action, taking charge of your brain, and breaking free from depression to find hope and happiness.
How your brain makes you depressed -- Managing your brain with medication -- Technique #1 : Identify triggers, plan new responses -- Technique #2 : Start where you already are -- Technique #3 : Cool down burnout -- Technique #4 : Mobilize your energy -- Technique #5 : End isolation -- Technique #6 : Balance your life -- Technique #7 : Prevent destructive behavior -- Technique #8 : Broaden your perspective -- Technique #9 : Increase flexibility -- Technique #10 : Learn to live fully.
Formerly CIP.
Includes bibliographical references (p. [275]-287) and index.
Keywords: Depression -- Popular works; Depression -- Prevention and control; Depression, Mental -- Prevention; Depression, Mental -- Popular works; Depression, Mental -- Prevention; Depression -- Popular Works; Depression -- prevention & control; Popular works